(−)-Epigallocatechin-3-Gallate Inhibits the Life Cycle of Pseudorabies Virus In Vitro and Protects Mice Against Fatal Infection - Huan, Changchao; Xu, Weiyin; Guo, Tingting; Pan, Haochun; Zou, Hengyue; Jiang, Luyao; Li, Chengmin; Gao, Song (Frontiers in Cellular and Infection Microbiology, 2021)
A newly emerged pseudorabies virus (PRV) variant with enhanced pathogenicity has been identiﬁed in many PRV-vaccinated swine in China since 2011. The PRV variant has caused great economic cost to the swine industry, and measures for the effective prevention and treatment of this PRV variant are still lacking. (–)-Epigallocatechin-3-gallate (EGCG) exhibits antiviral activity against diverse viruses and thus in this study, we investigated the anti-PRV activity of EGCG in vitro and in vivo. EGCG significantly inhibited infectivity of PRV Ra and PRV XJ5 strains in PK15 B6 cells and Vero cells. The anti-PRV activity of EGCG was dose-dependent, and 50 μM EGCG could completely block viral infection at different multiplicities of infection. We next revealed that EGCG blocked PRV adsorption and entry to PK15 B6 cells in a dose-dependent manner, but inhibition of PRV entry by EGCG was not as efficient as its inhibition of PRV adsorption. PRV replication was suppressed in PK15 B6 cells treated with EGCG post-infection. However, EGCG did not affect PRV assembly and could promote PRV release. Furthermore, 40 mg/kg EGCG provided 100% protection in BALB/c mice challenged intraperitoneally with PRV XJ5, when EGCG was administered both pre- and post-challenge. These results revealed that EGCG exhibits antiviral activity against PRV mainly by inhibiting virus adsorption, entry and replication in vitro. Meanwhile, EGCG increased the survival of mice challenged with PRV. Therefore, EGCG might be a potential antiviral agent against PRV infection.